PEMBUATAN BRIKET DARI KULIT KAKAO MENGGUNAKAN PEREKAT KULIT UBI KAYU - Rosta Natalia Sinaga; Rosdanelli Hasibuan (Talenta Publisher (Universitas Sumatera Utara), 2017)
This study aims to determine the effect of temperature variation carbonization, carbonization time and adhesive variation to charcoal characteristics of cocoa skin using cassava skin adhesive. Briquette is usually made using binder. Binder can embed charcoal each other to form strong and compact briquettes. Some other variables beside binder that influence the quality of briquettes include raw material, compacting presseure and carbonization process. This research used cocoa leather as raw material with cassava skin leaves as binder. All variables affect the content of fixed carbon of the briquettes that influence the caloricvalue of the briquettes. The caloricvalue is the most important factor for determining the quality of the briquettes. In this research, the highest caloricvalue of the briquettes was 4.375 cal/g. It was achieved when cocoa leather were carbonized by method 1 with compaction pressure of 85 kg/cm2 and binderconcentration of 15% where as raw material with particle size of 100 mesh. The caloricvalue of the briquettes was still very low and did not meet the qualification of Indonesian standard for briquettes. Based on the strength test, cassava skin leaves couldn’t be used as briquette’s binder. The produced briquettes that used cassava skin leaves as binder had soft structure and easily destroyed.